Lipid rafts mediate multilineage differentiation of human dental pulp-derived stem cells (DPSCs) - Santilli, Francesca; Fabrizi, Jessica; Martellucci, Stefano; Santacroce, Costantino; Iorio, Egidio; Pisanu, Maria Elena; Chirico, Mattea; Lancia, Loreto; Pulcini, Fanny; Manganelli, Valeria; Sorice, Maurizio; Delle Monache, Simona; et al. (Frontiers in Cell and Developmental Biology, 2023)
Cell outer membranes contain glycosphingolipids and protein receptors, which are integrated into glycoprotein domains, known as lipid rafts, which are involved in a variety of cellular processes, including receptor-mediated signal transduction and cellular differentiation process. In this study, we analyzed the lipidic composition of human Dental Pulp-Derived Stem Cells (DPSCs), and the role of lipid rafts during the multilineage differentiation process. The relative quantification of lipid metabolites in the organic fraction of DPSCs, performed by Nuclear Magnetic Resonance (NMR) spectroscopy, showed that mono-unsaturated fatty acids (MUFAs) were the most representative species in the total pool of acyl chains, compared to polyunsatured fatty acids (PUFAs). In addition, the stimulation of DPSCs with different culture media induces a multilineage differentiation process, determining changes in the gangliosides pattern. To understand the functional role of lipid rafts during multilineage differentiation, DPSCs were pretreated with a typical lipid raft affecting agent (MβCD). Subsequently, DPSCs were inducted to differentiate into osteoblast, chondroblast and adipoblast cells with specific media. We observed that raft-affecting agent MβCD prevented AKT activation and the expression of lineage-specific mRNA such as OSX, PPARγ2, and SOX9 during multilineage differentiation. Moreover, this compound significantly prevented the tri-lineage differentiation induced by specific stimuli, indicating that lipid raft integrity is essential for DPSCs differentiation. These results suggest that lipid rafts alteration may affect the signaling pathway activated, preventing multilineage differentiation.